2021
DOI: 10.21608/epsj.2021.159929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Fenugreek Seeds Powder as a Feed Additive in Broiler Chicks Diet on Growth Performance and Some Metabolic Responses

Abstract: This work was carried out to research the impact on growth performance, carcass characteristics, nutrient digestibility, some blood constituents and economic efficiency of the use of different levels of fenugreek seed powder (FSP) in growing Sasso chicks diet as a natural feed additive. A total of 120 unsexed Sasso broiler chicks, aged one day were divided into four care groups. There were three replicas of 10 birds each in each group. The 1 st group was fed a control diet, while the 2 nd , 3 rd and 4 th group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The nutrient retention in broilers maintained on the diets containing fenugreek seed powder and turmeric rhizome powder is pared to other groups. This finding is in accordance with [25] who reported addition of fenugreek seeds to broiler diets improved the digestibility of CP alone. Improving the digestibility of CP in birds fed diets supplemented with fenugreek seed powder might be due to long contact between digesta and mucosal epithelium might prolong the positive impact on intestinal morphology, which may be more efficient for nutrient digestion and absorption [26].…”
Section: Nutrient Retentionsupporting
confidence: 93%
“…The nutrient retention in broilers maintained on the diets containing fenugreek seed powder and turmeric rhizome powder is pared to other groups. This finding is in accordance with [25] who reported addition of fenugreek seeds to broiler diets improved the digestibility of CP alone. Improving the digestibility of CP in birds fed diets supplemented with fenugreek seed powder might be due to long contact between digesta and mucosal epithelium might prolong the positive impact on intestinal morphology, which may be more efficient for nutrient digestion and absorption [26].…”
Section: Nutrient Retentionsupporting
confidence: 93%
“…Highest values of total serum protein and creatinine were found to be 4.25 and 0.40, respectively in T6 group while lowest total serum protein and creatinine were found to be 3.55 and 0.32, respectively in T1 group. Similarly, Abdel-Azeem ( 2006) and Toson and Latif (2021) observed significant increase in total serum protein level in broilers fed fenugreek seed powder supplemented diet. The increase in total serum proteins might be due to the fact that fenugreek seeds can directly stimulate the thyroid gland and contribute to increased serum protein content (Hassan, 2000).…”
Section: Biochemical Parametersmentioning
confidence: 82%
“…However highest value of serum cholesterol was found in T1 group and lowest was found in T6 group. Abdel-Azeem (2006); Abbas (2010); Mamoun et al (2014); An et al (2015) and Toson and Latif (2021) also observed significant reduction in serum cholesterol level in broilers fed fenugreek seed powder and onion powder supplemented diet as compared to control group. The decrease in serum cholesterol level may be due to the presence of saponins and resins in fenugreek seeds (such as hemicelluloses, mucilage, tannin and pectin) that inhibit bile acid, help lower LDL-cholesterol and inhibit intestinal cholesterol absorption, thereby reducing blood cholesterol levels (Petit et al, 1995).…”
Section: Biochemical Parametersmentioning
confidence: 92%
“…Antibacterial, antifungal, anti-inflammatory, carminative, and antioxidant substances present in the mixture have boosted body gain [58]. The growth performance of Sasso broiler diet was increased by adding FRS powder (as natural feed additives) at level 1.0% [59].…”
Section: Growth Performancementioning
confidence: 99%